PENDAMPINGAN MAHASISWA DALAM PERSIAPAN DAN PELAKSANAAN INISIASI MENYUSU DINI DI PUSKESMAS WILAYAH BANJARNEGARA TAHUN 2019 - Retna, Rusfita; Sumanti, Reni (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2020)
Purpose: To determine the implementation of early breastfeeding initiation in the Banjarnegara District Health Center with student assistance in the preparation and implementation of IMD. Method: The research method used an experimental prospective approach in which the researcher conducted the research and followed the process of pregnancy until delivery and observing the initiation process for early breastfeeding. One Shot Case Study design is a design where a group is given treatment treatment and then the results are observed. The population of this study was pregnant women who gave birth at the Community Health Center in Banjarnegara in the period from March to May 2019. Accidental sampling was taken. Result: The results showed that the majority of physiological pregnant women and doing IMD were 60% (15 respondents), the majority of respondents gave birth normally and 79.2% (19 respondents) did IMD, most of the respondents were normal BBL and 70.4% (19 respondents ) doing IMD. Keywords: Assistance, Students, Early Breastfeeding Initiation.